Establishing a positive school identity through integrated curriculum and promotional strategies - Sri Diana Putri; Salwa Salsabila; Devina Amelia; Nabila Yusuf (Curricula: Journal of Curriculum Development, 2025)
In an era of globalization and increasing competition, entrepreneurship education has become essential for preparing students to face challenges in the workforce. This research aims to explore the implementation of entrepreneurship in schools as an innovative strategy to enhance the quality of education and the attractiveness of schools and explore how such innovations are strategically used as effective school promotion tools. The method used in this study is a qualitative approach, employing data collection techniques through in-depth interviews and observations at SMP Pandu, involving the principal, teachers, and students to gain a comprehensive perspective on the implementation of entrepreneurship and its impact on school management. The results indicate that the implementation of entrepreneurship at SMP Pandu not only increases student engagement in the learning process but also strengthens the school's image in the eyes of the community. The school has successfully utilized social media and digital marketing strategies to attract the attention of prospective students and parents and enhance participation in entrepreneurship programs. These findings are expected to contribute to the development of more effective and relevant educational policies.   Abstrak Dalam era globalisasi dan persaingan yang semakin ketat, pendidikan kewirausahaan menjadi penting untuk mempersiapkan peserta didik menghadapi tantangan di dunia kerja. Penelitian ini bertujuan untuk mengeksplorasi penerapan kewirausahaan di sekolah sebagai strategi inovatif untuk meningkatkan kualitas pendidikan dan daya tarik sekolah serta mengeksplorasi bagaimana inovasi tersebut digunakan secara strategis sebagai alat promosi sekolah yang efektif. Metode yang digunakan adalah pendekatan kualitatif, dengan teknik pengumpulan data melalui wawancara mendalam dan observasi di SMP Pandu, melibatkan kepala sekolah, guru, dan peserta didik untuk mendapatkan perspektif yang komprehensif mengenai implementasi kewirausahaan dan dampaknya terhadap pengelolaan sekolah. Hasil penelitian menunjukkan bahwa penerapan kewirausahaan di SMP Pandu tidak hanya meningkatkan keterlibatan peserta didik dalam proses belajar, tetapi juga memperkuat citra sekolah di mata masyarakat. Sekolah berhasil memanfaatkan media sosial dan strategi pemasaran digital untuk menarik perhatian calon peserta didik dan orang tua, serta meningkatkan partisipasi dalam program-program kewirausahaan. Temuan ini diharapkan dapat berkontribusi pada pengembangan kebijakan pendidikan yang lebih efektif dan relevan. Kata Kunci: inovasi pendidikan; kewirausahaan; penerimaan peserta didik baru; PPDB; promosi berbasis teknologi